DESIGN AND MODELLING OF ANCHOR PULLING USING FINITE ELEMENT METHOD ON SUBSEA PIPELINES - Azzahra Putri, Devina
Failure on subsea pipelines is caused by various factors; a common one is failure caused by ship anchors being dropped incorrectly. Interaction between anchor and ship can pull the pipeline over some distance so that it undergoes deflection and buckling. Interactions between anchor and pipe that might happen are impact, pull-over, and hooking. In this final project, the pipe behavior analyzed was caused by anchor hooking interactions, where the anchor stuck and wedged under the pipeline. Hooking loads form in vertical displacement with a duration of several minutes. Wall thickness design is done based on DNV ST F101, API RP 1111, ASME B31.8, and CSA Z662 to ensure pipe strength in resisting hoop stress. Concrete coating thickness design is also done based on DNV RP F109 to ensure pipe stability. After that, anchor pulling analysis is done using the finite element method by ABAQUS software to analyze the stress capacity of pipelines as a result of displacement loads and to see the buckling behavior of pipelines segment that interact with the anchor. The global behavior of pipelines is modeled using the beam element, while the local behavior is modeled using the shell element. Based on the design process that has been done, the determined value of wall thickness is 19.05 mm (0.75 inches), and the concrete thickness is determined to be 78 mm without trenching. Modelling anchor pulling results in the finding that anchor width and contact area between anchor and pipe influence the stress value in the pipeline. The smaller the anchor width value, the greater the tensile capacity and displacement value that the pipe can accept. Modelling the anchor in the form of a right-angled plate also increases the tension capacity compared to anchors in the form of a flat plate because the contact generated in the anchor model of the right-angled plate is more spread out and does not hold the curve of the pipe.